Pan-Bcl-2 inhibitor Obatoclax is a potent late stage autophagy inhibitor in colorectal cancer cells independent of canonical autophagy signaling. Issue 1 (December 2015) - Koehler, Bruno; Jassowicz, Adam; Scherr, Anna-Lena; Lorenz, Stephan; Radhakrishnan, Praveen; Kautz, Nicole; Elssner, Christin; Weiss, Johanna; Jaeger, Dirk; Schneider, Martin; Schulze-Bergkamen, Henning
Abstract Background Colorectal cancer is the third most common malignancy in humans and novel therapeutic approaches are urgently needed. Autophagy is an evolutionarily highly conserved cellular process by which cells collect unnecessary organelles or misfolded proteins and subsequently degrade them in vesicular structures in order to refuel cells with energy. Dysregulation of the complex autophagy signaling network has been shown to contribute to the onset and progression of cancer in various models. The Bcl-2 family of proteins comprises central regulators of apoptosis signaling and has been linked to processes involved in autophagy. The antiapoptotic members of the Bcl-2 family of proteins have been identified as promising anticancer drug targets and small molecules inhibiting those proteins are in clinical trials. Methods Flow cytometry and colorimetric assays were used to assess cell growth and cell death. Long term 3D cell culture was used to assess autophagy in a tissue mimicking environment in vitro. RNA interference was applied to modulate autophagy signaling. Immunoblotting and q-RT PCR were used to investigate autophagy signaling. Immunohistochemistry and fluorescence microscopy were used to detect autophagosome formation and autophagy flux. Results This study demonstrates that autophagy inhibition by obatoclax induces cell death in colorectal cancer (CRC) cells in an autophagy prone environment. Here, we demonstrate that pan-Bcl-2 inhibition by obatoclax causes a striking, late stage inhibition of autophagy in CRC cells. In contrast, ABT-737, a Mcl-1 sparing Bcl-2 inhibitor, failed to interfere with autophagy signaling. Accumulation of p62 as well as Light Chain 3 (LC3) was observed in cells treated with obatoclax. Autophagy inhibition caused by obatoclax is further augmented in stressful conditions such as starvation. Furthermore, our data demonstrate that inhibition of autophagy caused by obatoclax is independent of the essential pro-autophagy proteins Beclin-1, Atg7 and Atg12. Conclusions The objective of this study was to dissect the contribution of Bcl-2 proteins to autophagy in CRC cells and to explore the potential of Bcl-2 inhibitors for autophagy modulation. Collectively, our data argue for a Beclin-1 independent autophagy inhibition by obatoclax. Based on this study, we recommend the concept of autophagy inhibition as therapeutic strategy for CRC.